Spatial and temporal variability in coccolithophore abundance and distribution in the NW Iberian coastal upwelling system - Ausin, Blanca (2018)
A systematic investigation of the spatial and temporal variability in coccolithophore abundance and distribution through the water column of the NW Iberian coastal up-welling system was performed. From July 2011 to June 2012, monthly sampling at various water depths was conducted at two parallel stations located at 42 degrees N. Total coccosphere abundance was higher at the outer-shelf station, where warmer, nutrient-depleted waters favoured coccolithophore rather than phytoplanktonic diatom blooms, which are known to dominate the inner-shelf location. In seasonal terms, higher coccosphere and coccolith abundances were registered at both stations during upwelling seasons, coinciding with high irradiance levels. This was typically in conjunction with stratified, nutrient-poor conditions (i.e. relaxing upwelling conditions). However, it also occurred during some upwelling events of colder, nutrient-rich subsurface waters onto the continental shelf. Minimum abundances were generally found during downwelling periods, with unexpectedly high coccolith abundance registered in subsurface waters at the inner-shelf station. This finding can only be explained if strong storms during these downwelling periods favoured resuspension processes, thus remobilizing deposited coccoliths from surface sediments, and hence hampering the identification of autochthonous coccolithophore community structure. At both locations, the major coccolithophore assemblages were dominated by Emiliania huxleyi, small Gephyrocapsa group, Gephyrocapsa oceanica, Florisphaera profunda, Syracosphaera spp., Coronosphaera mediterranea, and Calcidiscus leptoporus. Ecological preferences of the different taxa were assessed by exploring the relationships between environmental conditions and temporal and vertical variability in coccosphere abundance. These findings provide relevant information for the use of fossil coccolith assemblages in marine sediment records, in order to infer past environmental conditions, of particular importance for Paleoceanography. Both E. huxleyi and the small Gephyrocapsa group are proposed as proxies for the upwelling regime with a distinct affinity for different stages of the upwelling event: E. huxleyi was associated with warmer, nutrient-poor and more stable water column (i.e. upwelling relaxation stage) while the small Gephyrocapsa group was linked to colder waters and higher nutrient availability (i.e. early stages of the upwelling event), similarly to G. oceanica. Conversely, F. profunda is suggested as a proxy for the downwelling regime and low-productivity conditions. The assemblage composed by Syracosphaera pulchra, Coronosphaera mediterranea, and Rhabdosphaera clavigera may be a useful indicator of the presence of subtropical waters conveyed northward by the Iberian Poleward Current. Finally, C. leptoporus is proposed as an indicator of warmer, saltier, and oligotrophic waters during the downwelling/winter regime.